An optimization framework for practical multipath routing in wireless mesh networks - Radunovic, Bozidar; Gkantsidis, Christos; Key, Peter; Rodriguez, Pablo; Hu, Wenjun (2007)
We consider wireless mesh networks, and exploit the inherent broadcast nature of wireless by making use of multipath routing. We present an optimization framework that enables us to derive optimal flow control, routing, scheduling, and rate adaptation schemes, where we use network coding to ease the routing problem. We prove optimality and derive a primal-dual algorithm that lays the basis for a practical protocol. Optimal MAC scheduling is difficult to implement, and we use random scheduling rather than optimal for comparisons. Under random scheduling, our protocol becomes fully decentralised. We use simulation to show on realistic topologies that we can achieve 20-200% throughput improvement compared to single path routing, and several times compared to a recent related opportunistic protocol (MORE).